A study on factors that influence customer purchase decision in online shopping / Rashidah Abdul Rashid - Abdul Rashid, Rashidah (2011)
This research paper is studied on factors that affect customer purchased decisions in online shopping. This studies will be conducted by the researcher to discussed about to what extent consumer purchased decision towards online shopping based on six major criteria which is product/ services available, payment method, price, security/ privacy concern, promotion and internet availability. Researcher want determine whether there is significance relationship between six factors determine with the customer decision to shop online. This study will be divided into 5 main chapters. The first part of this paper, the researcher will discussed about background of the study, problem statement, research objectives, theoretical framework, hypothesis, significance of study, definition of terms, and limitation of study and scope of the study. The objectives of this study is to identify what factors that influence customer who do and do not purchased product in online shopping. Second part of this paper, the researches discuss all six factors based on past literature research that obtain from journals, books and articles. In research methodology, researcher will discuss clearly researcher research plan. This part will cover the research design that is used in conducting marketing research project. All the method used to gain understanding and answers to the research objectives, research questions and the research hypotheses. This section discusses the methods used in the study. The scope that will be discuss including the research design, sampling and data collection, the instruments used for the research, measurement and scaling, and the procedure in data analysis. All the technique to develop the questionnaire and how it will be distributed to the respondent were also discuss in this part